ChemInform Abstract: Carbon Nanotubes in Cancer Therapy: A More Precise Look at the Role of Carbon Nanotube—Polymer Interactions. Issue 36 (15th August 2013) - Adeli, Mohsen; Soleyman, Rouhollah; Beiranvand, Zahra; Madani, Fahimeh
Abstract Review: 323 refs.